ANALISIS PERBANDINGAN PENDAPATAN PETANI SAWIT DENGAN PETANI SAWIT INTEGRASI PETERNAKAN AYAM PEDAGING (Broiler) di DESA AIR TERBIT KECAMATAN TAPUNG KABUPATEN KAMPAR - Putri, Dian Oktora Sudrajat; ', Cepriadi '; ', Kausar ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The purpose of this study is (1) to analyze the income of smallholders with the integration of broiler farms (Broiler) in the Water Village Publishing Tapung District of Kampar regency. (2) to analyze the efficiency of farming sawitdengan integration broiler farms (Broiler) in the Water Village Publishing Tapung District of Kampar regency.(3) Comparing the incomes of smallholders with the integration of broiler farms (Broiler) in the Water Village Publishing Tapung District of Kampar regency. This research was conducted by survey by questionnaire. While the sampling is done Random sampling is random sampling technique. Net income of smallholders with the integration of broiler chickens is higher than the net income of smallholders without integration of broiler chickens , namely Rp.130.749.886,42 and Rp.23.343.559,91. With high production costs in because raising broiler chickens also provides a high income for farmers. Average - Average RCR obtained smallholders without integration of broilers by 2.5 artinyas ach expenditure of Rp.1 petaniakan make a profit of Rp.2,5 . RCR obtained by smallholders with broilers sebesar2.6 integration means that any expenditure of Rp.1 farmers will make a profit of Rp.2.6 , this means that farmed broiler integration palm fositif give effect to oil palm cultivation. Based on farming activities without integration palm and palm growers with integrated broiler concluded that equally benefit from having acquired RCR greater than one (RCR > 1). Keyword: Revenue, Efficiency , Compariso